2007
DOI: 10.1016/j.ejphar.2007.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nicotinic and histamine H3 systems in the radial-arm maze repeated acquisition task

Abstract: Nicotinic systems have been found in a variety of studies to play important roles in cognitive function. Nicotinic involvement in different aspects of cognitive function such as learning vs. memory may differ. We have found in rats that the spatial repeated acquisition task in the radial-arm maze is significantly improved by low doses of the nicotinic receptor antagonist mecamylamine, the atypical nicotinic receptor ligand lobeline, as well as the α7 nicotinic receptor agonist ARR-17779. Interestingly, nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…In fact, it has been reported that H 3 Rs were involved in the reinforcing properties of certain drugs of abuse, such as, morphine [41], cocaine [10,42], amphetamine [10,43], nicotine [44], and 3,4-methylenedioxymethamphetamine "MDMA" [45]. More particularly, the present findings were in agreement with numerous studies that have demonstrated a relationship between H 3 R and alcohol abuse [2][3][4][5][6]46,47].…”
Section: Discussionsupporting
confidence: 94%
“…In fact, it has been reported that H 3 Rs were involved in the reinforcing properties of certain drugs of abuse, such as, morphine [41], cocaine [10,42], amphetamine [10,43], nicotine [44], and 3,4-methylenedioxymethamphetamine "MDMA" [45]. More particularly, the present findings were in agreement with numerous studies that have demonstrated a relationship between H 3 R and alcohol abuse [2][3][4][5][6]46,47].…”
Section: Discussionsupporting
confidence: 94%
“…While a number of studies found that acute nicotine administration (0.07 or 0.14 mg/kg) improved performance in the radial arm maze in rats [123-125], others found either an effect in aged but not young rats [126] or variable effects across experiments [127, 128]. Furthermore, some studies found a lack of an effect at the same doses of nicotine as used in prior studies [129, 130] and one experiment found a trend towards a deficit [131]. …”
Section: Spatial Working Memorymentioning
confidence: 99%
“…Levin and colleagues 42 recently studied the effects of nicotine and thioperamide by using the repeated acquisition test in the radial-arm maze. They first determined a dose of nicotine (0.4 mg/kg) that impaired task acquisition, and a dose of thioperamide (10 mg/kg) that increased errors in the task.…”
Section: Figmentioning
confidence: 99%